Pengembangan Media Pembelajaran Audio Visual Materi Bangun Ruang Sisi Datar di SMP Negeri 6 Mataram - Septiyana Kurnia Hartatin; Arjudin Arjudin; Nani Kurniati; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
The purpose of this research is to produce a learning audiovisual media that is suitable for the material of build a flat side room in SMP Negeri 6 Mataram. The method used in this research is according to Luther, is multimedia development life cycle (MDLC). MDLC have 6 steps, there are concept, design, material collecting, assembly, testing, and distribution. Field testing was used in this research are validation test, practical test, and test for the learning media’s effectiveness. In validation test, the result of this research is validated by some experts. The practical test was carried out by 2 practitioners and the test for effectiveness was based on the results of the questionnaire which were filled in by 74 students (37 students of class VIII and 37 students of grade IX). Instrumen indicators are based on the feasibility of the media according to Thorn. The results of the validation test showed an average score of 3.14, with a very good category. Meanwhile, the results of the practical test with an average score are 3.39 in the very good category, and the results of the effectiveness test with an average score of 2.86 in the good category. So it can be concluded that the audiovisual learning media that have been developed are suitable for use in learning mathematics.